Practice-based insights in developing and implementing a sport-based programme for girls. Issue 1 (2nd January 2019) - Collumbien, Martine; Das, Madhumita; Bankar, Shweta; Cislaghi, Beniamino; Heise, Lori; Verma, Ravi K.
ABSTRACT: Parivartan Plus is a structured sports mentoring programme for girls, implemented in a Mumbai slum where social expectations around gender-appropriate behaviour and good parenting restricts girls' mobility and visibility in public spaces. This article presents practice-based learning from developing and implementing programme theory to empower girls in achieving changes in their everyday social interactions at home and beyond. Gender and social norms theory were combined with local practical wisdom to turn main implementation challenges into opportunities. The article reflects on the strategies that gave visibility to, and achieved community endorsement for, the erosion of restrictive gender norms while ensuring community safety.